2011
DOI: 10.5194/nhess-11-2043-2011
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the Special Issue on Extreme and Rogue Waves

Abstract: No Abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The dispersive focussing can be explained by creating a long wave group with decreasing frequencies, then the dispersion forces the group to contract to a few wavelengths at a given position. This mechanism is also suggested in [18,7,11,19]. Reference [13] confirmed that extreme waves most likely occur due to the dynamics of a single wave group in agreement with the dynamics imposed by the Zakharov equation [20].…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…The dispersive focussing can be explained by creating a long wave group with decreasing frequencies, then the dispersion forces the group to contract to a few wavelengths at a given position. This mechanism is also suggested in [18,7,11,19]. Reference [13] confirmed that extreme waves most likely occur due to the dynamics of a single wave group in agreement with the dynamics imposed by the Zakharov equation [20].…”
Section: Introductionsupporting
confidence: 60%
“…Understanding the mechanism of freak wave appearance is important as it may cause damages in the ocean or shore. Indonesian region has the largest number of fatalities caused by freak waves [7,8]. On 1 January 2016, local media reported a freak wave up to 9m high came to the shore, specifically at Bantul Jati and Perawan Desa beach in Malang regency and dragged five people [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Onorato et al [3] proposed that the generation of rogue waves in different physical backgrounds and the physical quantities explained in different fields are also different. Pelinovsky et al [4] proposed formation mechanisms of deformed waves, such as dispersion focusing, the Benjamin-Feir instability, etc. An experiment using regular wave packets to pass through the positive current gradient region showed that the increase of wave steepness causes modulation instability and induces the development of largeamplitude water waves.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of a single high wave can be seen as resulting from an essentially linear constructive interference of numerous harmonics and the role of nonlinearity is limited to modification of the initial spectrum to the prescribed shape at the focusing locations identical phases of all harmonics [Shemer, 2016]. This mechanism is also suggested in Kharif and Pelinovsky [2003], Gemmrich and Garrett [2008], Pelinovsky and Kharif [2011] and Longuet-Higgins [1974]. Fedele [2007] confirmed that extreme waves most likely occur due to the dynamics of a single wave group in agreement with the dynamics imposed by the Zakharov equation [Zakharov, 1999].…”
Section: Mechanisms Of Extreme Wavesmentioning
confidence: 95%